(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Collemopsidium angermannicum (Degel.) A. Nordin (Xanthopyreniaceae, Dothideales) firstly reported for Ukraine from concrete channel building (Kakhovskiy district, Kherson Region). This lichen formed black zone above channel water level.